Analisis Perampingan Beban Kerja pada Bagian Packaging Material dengan Metode Workload Analysis - Yanto, Andri; Amrina, Uly (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
This research is based on the results of observations of working time in the Packaging Materials (PM) section of a nutritional beverage company which indicates idle time has a negative impact on company productivity. The research objective is to calculate and streamline the workload with the optimal number of workers in the PM section. The research method used is time and motion study with work load analysis based on lean concepts. A total of 30 samples were taken using simple random sampling method. Data were analyzed using a descriptive workload analysis method. The results showed that the existing workload of PM feeder operators had a workload of 82.92%, assistant feeder PM operators had a workload of 60.16%, and RMPM driver operators had a workload of 57.27%. In addition, the optimal number of workers in the packaging material preparation process is 2 people. Finally, improvements are proposed using a lean concept approach in allocating main and additional work elements to operators in the packaging material preparation process.